Vatican II : renewal within tradition - Lamb, Matthew L.; Levering, Matthew, 1971- (Oxford University Press, 2008)
From 1962 to 1965, in perhaps the most important religious event of the twentieth century, the Second Vatican Council met to plot a course for the future of the Roman Catholic Church. After thousands of speeches, resolutions, and votes, the Council issued sixteen official documents on topics ranging from divine revelation to relations with non-Christians. In many ways, though, the real challenges began after the council was over and Catholics began to argue over the interpretation of the documents. Many analysts perceived the Council's far-reaching changes as breaks with Church tradition, and.